PELATIHAN AGROPRENEUR MINDSET SISWA SMKM 5 GRESIK - Surianto, Moh Agung; Umaimah, Umaimah (Jurnal Pengabdian Masyarakat dan Lingkungan, 2024)
Strengthening the agropreneur mindset for students at SMK Muhammadiyah 5 Gresik; The only agricultural vocational school in Gresik Regency is important, considering that the vocational school only has two majors, namely agriculture and animal husbandry, both of which are related to the agricultural sector. The agricultural sector now and in the future will continue to grow along with population growth. This service program aims to strengthen the agropreneur mindset for SMKM 5 Gresik students so that it will contribute to the orientation of SMK graduates not only as job seekers but as job creators, able to absorb local workers, and help reduce the unemployment rate, especially at the Gresik Regency level. This service activity is carried out in the form of offline training at the Jalan Raya Surowiti School location, Sumurber Village, Panceng District, Gresik Regency. The results of the service show that there is an increase in the understanding of SMKM 5 Gresik students about the importance of strengthening the agropreneur mindset so that many entrepreneurial ideas emerge in the agricultural sector.